An assessment on the usage of different learning management systems in the University of the Philippines School of Library and Information Studies - Dacanay, John Finly G. (2011)
The use of e-learning in the majority of higher education institution is identified by the use of Learning Management Systems (LMS). Many colleges and universities maintain a Learning Management System that have a number of e-tools to cater the need of their students and teachers. The advantage of having one standard system is that the institution can concentrate on the technical and staff support of one system. Another advantage is whichever resources the instructor uploads can be made available to others, either to share good practice or to benefit a wider range of students than those inside his classes. The UVLe was created by the UP DILC to address this need of the teachers and students of the university for a Learning Management System. But in spite of the existence of the university's own Learning Management System, majority of the teachers in UP SLIS still use other systems like Yahoo! Groups, Google Groups and EDU 2.0 to support their teaching.